Marginal cost analysis approach to production engineering enterprises (Economics and region, 2018)
The traditional procedure for determining the production cost of different types of products provides enterprise engineering division of indirect costs in accordance with the selected base, which leads to inaccuracies in the formation of production costs in general and discards relationship between cost and profit. However, using elements of marginal analysis as part of management accounting, industrial enterprises have the ability to more accurately analyze the impact of the structure of production costs and revenues to the profitability of manufactured products. This method of analysis by simulation will look for the most favorable ratio between variable and fixed costs, cost of production and volume production. In this regard, the urgent task is to study: marginal impact factors on the change in income; stage application element of margin calculation of production costs, taking into account the organizational and technological features of the machine-building enterprises in Ukraine.Marginal analysis helps identify the optimal proportion between the cost price and sales volume, to determine for each sales situation, providing a break-even business. The key indicators of marginal analysis are: variable and fixed costs, profit margin, a critical output (threshold of profitability, break-even point), stock of financial strength, the effect of production (operating) lever.Use marginal costing approach must first determine the list of fixed and variable costs and the cost include only those items that affect the amount of the cost of production and controlled business units.The difference between revenue from sales and variable costs is marginal income for each product. Its value indicates the amount of coverage that characterizes the contribution of each product to the formation of the overall financial result.The next step marginal analysis is an analysis of the actual cost of production of certain products and articles for the results of the company. Therefore, specific types of products will be defined regulatory costs based on volume of sales.Formation of financial results takes place in two stages:Determine the profit margin.Determine the overall financial result for the company (marginal income deducted from the fixed costs of the enterprise as a whole).The final stage of analysis is to determine the deviation of actual costs of standard, pre-adjusted volume of sales.Analysis of the impact of various factors on the value of marginal income made based on the following parameters: deviation marginal income by total sales of products (product of the difference between the actual and planned volume of realization in the required profit margin per unit); deviations marginal income by selling price (the product of the difference between actual and normative price of actual sales); deviation margin income on variable costs (product of the difference between the actual variable and standard costs to actual sales).Thus, the use of marginal approach the analysis only variable costs, the value of which depends on the volume of sales. Fixed costs remain unchanged when changing the sales and expenses belong to the reporting period. This analysis reflects the variable costs rejection of marginal income. Since the value of marginal income per unit is not changed, unlike profits, which is the largest variable. Obviously the fact that deviations marginal income is identical deflection overall financial result. So, in order to control costs and operating profit in the mechanical engineering required is to calculate the marginal income on the basis of "direct costing" and the implementation of its analysis.Consequently, the results of research in the reasoned feasibility of implementation activities engineering companies marginal analysis to predict the effects of short-term management decisions based on real business results depending on a variety of factors
Keywords: marginal analysis; production costs; profitability; sales